Game Programming: Arabic Words Puzzle. - M. AbdAllah, Israa; B.Jamil, Afaf; S.Jasim, Zeina; A.Daood, Abeer (Iraqi Journal of Science, 2023)
This research shows the design and implementation of a small and simple Arabic word-puzzle game to test the effect of electronic games in enhancing and supporting the traditional learning system. The system based on from the real needs of classrooms in the Iraqi primary schools so the game is designed for primary school students (first and second grade) and this required the exploration of how schools use and teach information. The system is built by using Visual Basic version 6 programming language in conjunction with the Microsoft Office Access 2007, Results show our game based educational program is effective. 14 children (6-7 years old) played the game. The children played through multiple sessions. For each child; this game is useful in learning new words and enhance his/her memory by repetition